Analisis Kesulitan Membaca Permulaan Pada Siswa Sekolah Dasar - Rahmah Kumullah; Ahmad Yusuf; Haslinda Haslinda; Salmiati Salmiati; Amrullah Mahmud (STKIP Andi Matappa Pangkep, 2021)
This study discusses the difficulty of reading beginning in grade I at SDN No.31 Tumampua V in Pangkajene and Islands districts with a total of 18 students but 13 students experiencing difficulty reading at the beginning. Pre-reading ability is a basic ability at the basic education level and elementary school is an educational unit that provides basic abilities. This research is a descriptive study with a quantitative approach. Data collection using tests, observation, and documentation. Data analysis using non-statistical analysis. The results of this study showed that the highest difficulty aspect of students in pre-reading was the difficulty in reading meaningless words with a score of 16%. Difficulty reading at the beginning of the next is in the aspect of fluency in reading aloud and reading comprehension with a score of 27%. Another difficulty experienced by students was the difficulty in reading words, which was 33%. Then the difficulty in recognizing letters with a score of 51%. The last aspect of reading difficulty was listening or listening comprehension, which was 79%.